PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA MATERI KESETIMBANGAN ION DAN PH LARUTAN PENYANGGA - Yolanda Ariska; Johni Azmi; Betty Holiwarni (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2020)
The purpose of this study was to improve student learning achievement in ion and pH equilibrium material and applied on class XI MIA SMA Negeri 9 Pekanbaru. This research is an experimental research using pretest-posttest. The implementation of this research in Pekanbaru 9 High School with the sample of this study was the XI MIA 2 students who were the experimental class and the XI MIA 3 students were the control class. Where the experimental class is a class that is applied cooperative learning models, while the control class does not apply the learning model. In this study the data used by the t-test data analysis technique. From the data analysis test results obtained t count > t table is 3.74> 1.66, with the meaning that the application of cooperative learning models can improve student achievement on the subject of ion balance and pH of buffer solution in class XI MIA SMA Negeri 9 Pekanbaru.